Range values for external and internal intensity monitoring in female soccer players: a systematic review - Oliveira, Rafael (2022)
Background: The range values of different training and match intensity measures obtained to define benchmarks in female soccer players are needed. Usually, cohort studies analyse only one team with a relatively small sample size, which brings forth the need for a systematic review to generalise training and match intensity evidence. Objectives: This review aimed to identify and summarise studies that have examined external and internal training or match intensity monitoring to provide range values for the main measures in female soccer players. Methods: A systematic review of EBSCO, PubMed, Scielo, Scopus, SPORTDiscus and Web of Science databases was per formed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: From the 2853 studies searched, 44 were analysed in which the following range intervals were found for training: rated perceived exertion (RPE, 1–7 AU), session-RPE (s-RPE, 51–721 AU), total distance (2347–6646 m) and distance >19.4 km·h−1 (9– 543 m). For matches, the range values were s-RPE (240–893 AU), total distance (5480–10581 m), distance≥14 km·h−1 (543–2520 m), ≥ 18 km·h−1 (96–1680 m), number of accelerations (49–240) and deceleration (21–85) and player load (848–1096 AU). Conclusions: This study provides range values of s-RPE, RPE, TRIMP, total distance and distance >19.4 km·h−1 regarding training; range intervals of s-RPE, heart rate average and maximum, total distance, distance ≥ 14 km·h−1 , ≥ 18 km·h−1 , ACC and DEC (> 2 ms−2 ) regarding matches for professional female players that can be used by coaches, practitioners or researchers to achieve similar training and competitive levels.